The Effect of Using Pictionary Game Towards Students Vocabulary Mastery at Tenth Grade Student of Senior High School 8 Jambi - Nur Anisah; Yanti Ismiyati; Efa Silfia (Universitas Batanghari Jambi, 2023)
The researcher was conducted based on the problem the students in learning English especially in vocabulary mastery. The researcher said that inthis study he used two classes. Researchers use this test as a tool to obtain data consisting of vocabulary tests. The test used is a multiple-choice test designed to identify the impact of the use of picture games on students' vocabulary. These test results are further analyzed for the impact of picture play on increasing students' vocabulary. Researchers calculated the data using quantitative analysis. Researchers tested the hypothesis using a t-test formulation. The survey results showed that the average score of the experimental class was 55.33 before applying the picture play technique. The control class average score was 56.88. On the other hand, after applying the picture game technique, the test class average is 64.77. The control class average score was 62.77. The researchers found t-test results with t0 higher than tt - t0 was 5.835 and tt was 1.669 (5.835 > 1.669). This means that Ha was accepted and H0 was rejected. The conclusion of this study is that there was a significant effect of picture play techniques on her 10th grade vocabulary skills in Senior High School 8 Jambi.